2010
DOI: 10.4103/0970-1591.60441
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic pyeloplasty in pediatric patients: The SGPGI experience

Abstract: Objectives:To determine the safety, efficacy and long-term outcome of laparoscopic pyeloplasty in pediatric patients.Materials and Methods:A prospective analysis of data of pediatric patients under the age of 15 years, who had undergone laparoscopic pyeloplasty from January 2000 to June 2008 was done. The various parameters analyzed were; operative time, blood loss, need for analgesics, intra/postoperative complications, hospital stay and postoperative outcome. Success was defined on the basis of either improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
(40 reference statements)
1
4
0
Order By: Relevance
“…The other 2 serious complications (urinoma and sepsis) occurred in a group of patients without the use of ureteral stents. In this aspect, our data are corresponds to the literature, which indicate the same complications in the group of patients without ureteral stenting [9]. Among the of kidney abnormalities concomitant with the UPJ stenosis, the horseshoe kidney attracts attention.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The other 2 serious complications (urinoma and sepsis) occurred in a group of patients without the use of ureteral stents. In this aspect, our data are corresponds to the literature, which indicate the same complications in the group of patients without ureteral stenting [9]. Among the of kidney abnormalities concomitant with the UPJ stenosis, the horseshoe kidney attracts attention.…”
Section: Discussionsupporting
confidence: 85%
“…The advantages of laparoscopic pyeloureteroplasty over open surgery are the possibility magnified vision, low morbidity regarding the postoperative analgesia and shorter hospital stay, minimal incision site scar. However, it is still a more lengthy procedure with higher re-treatment rate (7 -18%) as compared to OP [3,9].…”
Section: Discussionmentioning
confidence: 99%
“…Maheshwari et al in a series of 82 patients encountered CV in seven children (8.5%) with age ranging from 4 months to 15 years (mean 7.12 years) 8 . In comparison, Assem et al reported an incidence of 17.39% in four out of 23 adolescents aged between 16 and 20 years 9 .…”
Section: Discussionmentioning
confidence: 94%
“…CVs are very rarely noticed in newborns and infants. According to the literature, the average age of patients with a CV is between 7 and 11 years and is statistically higher than in patients with pure intrinsic obstruction ( 8 12 ). In our material, the median age at surgery was 6 years in both groups.…”
Section: Discussionmentioning
confidence: 99%